THE I-XE RECORD OF ALTERATION IN THE ALLENDE CV CHONDRITE - Pravdivtseva O.V.; Krot A.N.; Hohenberg C.M.; Meshik A.P.; Keil K.; Weisberg M.K. (My University, 2003)
Complex I-Xe and mineralogical studies have been performed on four heavily-altered Allende fine-grained spinel-rich Ca, Al-rich inclusions (CAIs) and four Allende dark inclusions (DIs) showing various degrees of iron-alkali metasomatic alteration. The CAIs are largely composed of Fe-rich spinel, Al-diopside, and secondary nepheline and sodalite. The DIs consist of chondrules and Allende-like matrix composed of lath-shaped fayalitic olivine, nepheline, sodalite, and Ca, Fe-rich pyroxene ± andradite ± FeNi-sulfide nodules. Chondrule phenocrysts are extensively or completely replaced by fayalitic olivine, nepheline, and sodalite; metal nodules are replaced by FeNi-sulfides, andradite and Ca, Fe-rich pyroxenes. The chondrules and matrices are crosscut by Ca, Fe-rich pyroxene ± FeNi-sulfide ± fayalitic olivine veins. DIs are surrounded by continuous Ca-rich rims composed of andradite, wollastonite, kirschsteinite, and Ca, Fe-rich pyroxenes, whereas the outer portions of the inclusions are depleted in Ca.
Keywords: Allende chondrite